Design a tutorial to implement Communication experiences (Journal of the College of Basic Education, 2023)
This research deals with the implementation of several experiments used in the communication laboratory, where they were implemented using the mutisum.version 10 program. The electronic circuit components used in the experiment were easily linked despite the complexity of the electronic components used, as well as benefiting from simulation in the program for the purpose of obtaining practical results accurately and in a quick time. The computerized educational program was also designed and built based on the systems entrance methodology to provide students with the knowledge base of the subject of inclusion, and the computerized educational program takes into account individual differences, as the learner is not required to proceed according to the sequential arrangement of the units, but rather he can skip more units than these units according to his needs, abilities and speed of learning.